Warmer ecosystems save their breath - Johnston, Alice S. A. (Springer, 2025)
Land stores vast amounts of carbon, and how much of it is released as temperatures rise could accelerate climate change. Now research shows ecosystems are more adaptable to climate warming than previously thought, potentially reducing future carbon–climate feedbacks.
Keywords: Biogeochemistry; 31 Biological Sciences; 3103 Ecology; 13 Climate Action; 15 Life on Land